A clinical study of chronic pancreatitis. Issue 3 (September 1963) - Fitzgerald, Oliver; Fitzgerald, Patrick; Fennelly, James; McMullin, Joseph P.; Boland, Sylvester J.
Abstract : A series of 53 cases of chronic pancreatic disease is described and attention drawn to the frequency with which symptoms are persistent rather than intermittent. A plea is made for the use of the term `progressive' rather than `relapsing' in describing many of these cases. Alcohol was an unimportant factor in the aetiology. The possibility of achieving an accurate and early diagnosis using the serum secretin/pancreozymin test is emphasized. The frequent relief of symptoms and the prevention of progress of the disease by surgery, especially sphincterotomy, is recorded.